(untitled) (American Journal of Islam and Society, 2008)
The resources for instructors dealing with the Qur’an in their courses have improved in recent yearswith the completion of Jane DammenMcAuliffe’s Encyclopaedia of the Qur’an (Brill: 2001-06) and Cambridge Companion to the Qur’an (Cambridge University Press: 2006) and Andrew Rippin’s Blackwell Companion to the Qur’an (Balckwell: 2006). But however useful the collected articles of these works are, new students of the Qur’an often respond more enthusiastically to such narrative approaches as the vignettes in Bruce Lawrence’s The Qur’an: A Biography (AtlanticMonthly Press: 2007). The more integrated narrative approach of Ingrid Mattson’s The Story of the Qur’an: Its History and Place in Muslim Life provides a new accessible introduction to the Qur’an and its history. Mattson illuminates the perspectives of believers and critical historical scholarship by telling the story of the continuities and ruptures in the reception, transmission, and interpretation of the Qur’an among diverse communities in changing historical contexts ...